Microfinanzas y su repercusión en la sostenibilidad de los negocios del segmento agrícola del cantón buena fe, año 2023 - Barros Zambrano, Yuli Mabel (2025)
This research was conducted in the Buena Fe town, in 2024. Its main objective was to evaluate microfinance and its impact on the sustainability of agricultural businesses. Primary data were collected through an interview with the manager of a microcredit institution, a focus group with agricultural association directors, and a survey of the Buena Fe rural population. The research found that microcredit in agricultural businesses, from the perspective of the microcredit manager, has allowed many agricultural businesses to become sustainable. For their part, the association directors indicated that the impact of the microfinance they received has not been high because the interest rates charged by microcredit providers are high (24.89%). According to the agricultural entrepreneurs, economic sustainability has improved due to access to microcredit; they have experienced an increase in their production and family income, despite not having received training in microcredit management and needing that knowledge. Based on the above, the following sustainability strategies are proposed to overcome the challenges of microcredit: "Increasing the support and impact of microcredit on the development of agricultural businesses in the Buena Fe Canton," "Overcoming the main challenges and risks of microcredit," "Improving profitability levels," "Identifying factors that influence the sustainability of agricultural businesses that depend on microcredit," and "Financial counseling and training."